Planting arrangement, nitrogen resources and plant density on some vegetative characteristics of Melissa officinalis - Damavandi, Zahra; Sayfzadeh, Saeed (Ciência e Natura, 2015)
In order to study the effect of nitrogen supply resources, planting arrangement and bush density on some vegetative characteristics in Melissa, an experiment was conducted as split-split- plot based on randomized complete blocks design with three replications in Takestan region in 2013. Planting arrangement were placed in two levels of diamond and square in main plots, nitrogen supply resources in three levels of chemical fertilizer, manure and vermicompost in sub plots and bush density in three levels of 30 × 30 cm, 40 × 40 cm and 50 × 50 cm in sub sub plots, too. Traits such as bush height, stem diameter, number of leaves per bush, leaf and stem dry weight and lateral branches were Measured. The results indicated that greatest bush height, number of leaves and lateral branches and dry weight related to usage of nitrogen fertilizer. The greatest stem diameter, lateral branches and stem dry weight related to diamond arrangement. Also, the greatest bush height and leaf dry weight related to density of 30×30 cm, the greatest lateral branches, number of leaves per bush and stem dry weight related to 40 × 40 cm density and the highest stem diameter related to 50 × 50cm density. The highest bush height, stem dry weight and number of leaves per bush belonged to square arrangement × chemical fertilizer × bush density of 30 × 30 cm interaction treatment. Also, the greatest stem diameter and number of lateral branches belonged to diamond arrangement × manure fertilizer × bush density of 40 × 40cm.